Technology as experience - MacCarthy, John, ....-; Wright, Peter, 1935- (Cambridge (Mass.) : MIT, 2004)
1. Living with technology. 2. Going on from practice. 3. A pragmatist approach to technology as axperience. 4. The threads of experience. 5. Making sense of experience. 6. An online shopping experience. 7. A pilot's experiences with procedures. 8. Experiences of ambulance control. 9. Technology as experience
Keywords: Mens-computer interactie; Wetenschap